A comparison between Metformin immediate-release and extended-release: a review - Alshadfan, Hisham; Aljohani, Samar; Mirghan, Hyder; Abdullah, Muhammad Nazrul Hakim (National Institute of Health Sciences, 2022)
Metformin is the first-line oral therapy for type II diabetes; it comes in various forms that can be used alone or with other oral hypoglycemic medications. The National Institute for Health and Care Excellence guidelines recommended starting with Metformin immediate-release and shifting to extended-release when not tolerated. We aimed to compare the immediate and extended-release formulation in terms of metabolic profile, gastrointestinal adverse effects, patients' satisfaction, and health-related quality of life. The extended-release formulations were better in terms of gastrointestinal side effects. In addition, it improved patients' satisfaction and adherence to treatment. There were no significant differences between Metformin-immediate release (MIR) and Metformin-extended release (MXR) regarding body mass index and waist circumference. The effect on lipid profile was modest; a reduction of low-density lipoproteins, total cholesterol, and an increasing high-density lipoprotein were observed with no statistical significance between the two formulations. However, a rising triglycerides was found among patients taking the extended-release. The evidence is conflicting regarding glycemic control. Six out of the eight included studies showed similar efficacy, one showed the superiority of the immediate-release, and another one showed that the extended-release was more effective. Therefore, studies into hypoglycemia risk and lactic acidosis are definitely needed to address all these conflicting situations.